Antibiotic prescription patterns and associated symptoms in children living with HIV at Arthur Davison Children’s Hospital in Ndola, Zambia - Jonathan Gwasupika; Davidson H. Hamer; Victor Daka; Ephraim Chikwanda; David Mwakazanga; Ruth L. Mfune; Choolwe Jacobs (PLoS ONE, 2025)
Background Children with human immunodeficiency virus (HIV) infection are disproportionately susceptible to bacterial infections. There are a wide range of antibacterial agents available to manage HIV positive children with bacterial infections. However, administration of antibiotics in most children is empirical which could lead to antimicrobial resistance. Objectives This study aimed to determine commonly prescribed antibiotics and associated symptoms in children at Arthur Davison children’s hospital antiretroviral therapy clinic in Ndola, Zambia. Methods This was a cross-sectional study that analysed the antibiotic prescribing patterns from routinely collected secondary data at Arthur Davison children’s hospital. Children diagnosed with HIV before the age of 5, actively attending antiretroviral therapy clinic identified by SmartCare software and who had taken antiretroviral therapy for at least 6 months were eligible. Data were collected from files of children who met the eligibility criteria. STATA software version 16 SE (STATA Corp., College Station, Texas, USA) was used for analysis. A p-value less than 0.05 was considered statistically significant at a confidence interval of 95%. Results From a total of 132 children included in the study, 37.9% presented with symptoms with the most common symptoms being cough (70.0%) and diarrhoea (30.0%). A larger proportion of children (62.1%) were on arbacavir/lamivudine/dolutogravr combination of antiretroviral therapy while 8.2% were on the tenoforvir alafenamide/lamivudine/dolutobravir regimen. Children who were on abacavir/lamivudine/dolutegravir regimen presented with more symptoms (48.8%) compared to those on tenofovir alafenamide/lamivudine/dolutegravir (21.0%) and tenofovir disoproxil fumarate/lamivudine/dolutegravir (18.2%) (p = 0.006). Approximately 60.0% of children presenting with symptoms were prescribed antibiotics. Co-trimoxazole was the most commonly (38.0%) prescribed, while erythromycin (2.0%) and Cephalexin (2.0%) were the least. Conclusions Respiratory and gastrointestinal symptoms were the most common presentations suggestive of a suspected infection requiring antibiotic prescription in HIV-positive children on ART. Despite co-trimoxazole being the prophylactic drug among HIV-positive children, it was the most common antibiotic among children presenting with symptoms suggestive of an infection. This calls for the prudent use of co-trimoxazole to avoid its resistance.